(untitled) (Repertorio Científico, 2021)
Adenium obesum is a plant of the Apocynaceae family with high ornamental value. The attractiveness and diversity of its flowers together with the portion of thickened stem that it presents, give it a high attractiveness. In spite of being a highly appreciated plant in gardening and highly commercialized, there are very few studies on genetics. The market for ornamental plants requires the constant creation of new varieties of A. obesum in order to increase supply, however, the genetic improvement that has been carried out on the specie has been conventional by means of crosses and haven’t used biotechnology techniques. Objective: to consolidate all that is known about the genetics of A. obesum in order to create the basis for a future breeding program. Aspects such as: general characteristics of the species, floral morphology, propagation methods, manual pollination, self-incompatibility and different techniques that can support a breeding program were taken into account.